E-Learning System Audit in Engineering Faculty of Nurul Jadid University using Cobit 4.1 Framework - Nadhiroh, Anis Yusrotun; Hikmah, Durratul (Journal of Information Technology and Computer Science, 2018)
Engineering Faculty of Nurul Jadid university has an adequate IT support in teaching-learning process, it is e-learning system. However, this system is poorly exploited by users due to a lack of awareness in the importance of information. This study aims at measuring how far the e-learning system performance works as students and lecturers’ service by doing audit e-learning system. The audit refers to COBIT 4.1 standard specially for domain Deliver and Support (DS). Research method is conducted by determining domain, control process, indicator, and mapping the maturity level. The result shows that after auditing the e-learning system, it recommends an improvement on security system in DS 5 process with index 3.11 and DS 7 process with index 3.14 i.e. providing a training for users.